2021
DOI: 10.1007/s11684-021-0884-z
|View full text |Cite
|
Sign up to set email alerts
|

Biosensor-based assay of exosome biomarker for early diagnosis of cancer

Abstract: Cancer imposes a severe threat to people’s health and lives, thus pressing a huge medical and economic burden on individuals and communities. Therefore, early diagnosis of cancer is indispensable in the timely prevention and effective treatment for patients. Exosome has recently become an attractive cancer biomarker in noninvasive early diagnosis because of the unique physiology and pathology functions, which reflects remarkable information regarding the cancer microenvironment, and plays an important role in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 148 publications
(161 reference statements)
0
14
0
Order By: Relevance
“…Transmission electron microscopy showed that the exosomes had circular structures (Figure 2b). Because certain proteins highly enriched in exosomes, such as HSP70, CD9, CD82, Tsg101, and CD63, are used as markers to identify exosomes (Deng et al, 2022), including SC exosomes (Wei et al, 2019), we validated their expression in the isolated particles (Figure 2c). Our results are consistent with exosome characteristics (Wei et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Transmission electron microscopy showed that the exosomes had circular structures (Figure 2b). Because certain proteins highly enriched in exosomes, such as HSP70, CD9, CD82, Tsg101, and CD63, are used as markers to identify exosomes (Deng et al, 2022), including SC exosomes (Wei et al, 2019), we validated their expression in the isolated particles (Figure 2c). Our results are consistent with exosome characteristics (Wei et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Finally, exosomes were purified using a qEVoriginal/35 nm Gen 2 column (ICO‐35, Izon Science, Bellaire, TX, USA). Fractions of 2 mL were eluted with PBS, and the protein composition was analyzed by immunoblotting using antibodies targeting exosome markers HSP70A8, CD9, and CD81 (Deng et al, 2022; Mathieu et al, 2021). Exosome‐positive fractions were collected for subsequent experiments.…”
Section: Methodsmentioning
confidence: 99%
“…Exosomes are cell-secreted, nanosized bilayer membrane extracellular vesicles with diameters ranging from 40-100 nm [6]. Exosomes can carry a diferent number of bioactive molecules, including proteins, DNA, various types of RNAs (such as miRNAs, mRNAs, lncRNAs, and circular RNAs), lipids, and metabolites according to the cells of origin via cellular communication [7][8][9]. Exosomes were initially viewed as waste products produced during diferent physiologic cell metabolisms [10].…”
Section: Introductionmentioning
confidence: 99%
“…In turn, various abnormal biological alterations of diferent cells (including tumor cells) can also be refected by detecting the expression of exosomal molecules (including miRNAs) in body fuids [14]. Recent studies have shown that tumor cells can secrete many more exosomes than normal cells, and abnormal exosomes can be easily detected in various body fuids, such as urine, saliva, ascites, or blood [9]. Many studies have shown that the abnormal expression of miRNA in tumor exosomes is closely related to various biological changes, such as angiogenesis, tumor invasion, and metastasis [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…A biosensor is a device that can produce a measurable signal proportional to the concentration of the biological analyte target [6,7]. Biosensors are one of the most widely studied topics due to their contributions to development of innovative medicines, which could be applied as adapted drugs or highly sensitive detectors of disease markers [8][9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%